FAKTOR YANG BERHUBUNGAN DENGAN SISA MAKANAN PADA PASIEN KANKER DI RSUD Prof. Dr. MARGONO SOEKARJO PURWOKERTO - Fasehah, Siti; Rahmawati, Ana Yuliah; Noviardhi, Astidio (Poltekkes Kemenkes Semarang, 2017)
Background: Prevalence of inpatient cancer patients in RSUD Prof. Dr. Margono Soekarjo Purwokerto in the Bougenvil ward from May to August 2016 reached 1230 patients per month. Data on food waste in cancer patients at RS Dadi Family Purwokerto in July - September 2016 was showed how much the patient's remaining food is 33%. Evaluation of food waste is very important as evaluation that can be used as indicator of hospital nutrition service success.Research Object: to know the relation between indigestion, psychological condition, appearance and taste of food in diabetic patient in RSUD Prof. Dr. Margono Soekarjo Purwokerto.Research Method: Type of descriptive analytic research and cross sectional study design.Sampling method using purposive random sampling technique. Data analysis using Chi Square testResult: There is a relationship of indigestion with food waste (p = 0,002), there is relation of food appearance with food waste (p = 0,000), there is relation of food taste with food waste (p = 0,000), and there is no relation of psychic condition with food waste (p = 0.204)